The embossed technique on metal plate (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
The embossed technique on a metal plate, unlike the print engraving, is used to perform artistic works mainly on copper, brass, silver and gold so as to obtain an ornamental pattern in relief. The toreutica, which is part of its own artistic sphere, focuses on works of greater size and weight with respect to a metal plate, mainly dealing with the production of vases, cups, trays, weapons, etc. Therefore, within this same technique the intervention scale can vary from the jewel to the large vase, up to that of the large statue composed of several embossed plates. This art has existed since prehistoric times being practiced since the Copper Age by the inhabitants of Mehrgarh in South Asia (current Pakistan) who already used it between 7700 and 3300 B.C.. During the third millennium B.C. in the Middle East different methods were already in use to make more efficient the production of an embossed plate that was pressed and worked with wooden instruments on bas relief matrices made of stone, bones or metal. In Roman times, however, it is mentioned by Pliny the Elder (1st century A.D. in the XXXIII book of his Naturalis Historia) where he includes the Greeks Mentor, Acragante, Boeto and Mys being among the most famous chisellers. Unlike the dry point engraving, the emboss of the plate with this technique is obtained through the use of chisels, steel rods shaped in various ways to obtain the desired profiling and bending by applying pressure on very thin copper, tin, gold and silver. This pressure can be exerted by each of the two sides of the foil, so as to obtain the desired concavity–convexity effects. The smaller chisels are used to obtain a greater definition of the lines, while those of greater thickness are useful for creating and accompanying the effects of crowning. In the case of embossing very thin plates, which may even be 0,1 mm thick, at the end of the work the foil is generally reinforced by filling the voids with wax, plaster, rubber or other material, so as to prevent deformation of the bas relief. The analogous French term is repousséche, being the Italian one sbalzare, which means pulsing, pushing, embossing, thus referring to the idea of altering the coplanarity of the mouldable surface through a push, in many cases obtained by hammer percussion.